An examination of changes in autumn Eurasian snow cover and its relationship with the winter Arctic Oscillation using 20th Century Reanalysis version 3 - G. J. Marshall (The Cryosphere)
Utilising the 20th Century Reanalysis version 3 (20CRv3), we examine changes in the extent and rate of autumn Eurasian snow cover (SC) advance and the temporal variability in the SC–Arctic Oscillation (AO) relationship. Novel aspects are (i) analysis back to 1836, (ii) adjusting the reanalysis SC through comparison with observations, and (iii) analysing the statistical significance of the frequency of periods of significant SC–AO relationships to determine whether these connections can be distinguished from stochastic processes. Across the full span of 20CRv3, there is a small increase in mean September Eurasian SC. In contrast, there have been significant decreases in both October and November SC. Trends over the past 50 years demonstrate a slowing and accelerating of snow advance in October and November, respectively, corresponding to a postponement of SC onset. Robust relationships exist between September and October Eurasian SC and the winter AO across the 180-year span of 20CRv3. Within Eurasia, we reveal a strong SC–AO relationship with September SC in northeastern Eurasia, which has not been noted previously. The associated spatial pattern of September tropospheric height anomalies closely matches the positive phase of the western Pacific teleconnection pattern. As many other factors are known to impact the winter AO, and these predominantly occur in October or November, the residual September SC signal-to-noise ratio in the winter atmosphere is small. Therefore, model experiments in which only the magnitude of September SC is perturbed will be necessary to elucidate the processes behind this newly described SC–AO relationship.